PENGARUH PRETREATMENT MAKROALGA ULVA RETICULATA MENGGUNAKAN MICROWAVE IRRADIATION UNTUK PRODUKSI BIOETANOL - Kolo, S. M. D.; Obenu, N. M.; Tuas, M. Y. C. (Jurnal Kimia (Journal of Chemistry); Vol. 16, No.2, Juli 2022, 2022)
The production of fossil fuels every year until now has decreased significantly. This is in line with the significant increase in energy consumption as a result of increasing population, economic growth, industrial and transportation activities. Alternative energy that can be used as a substitute for fossil fuels is the use of macroalgae Ulva reticulata into bioethanol. The lignocellulosic content of Ulva reticulata can be converted into ethanol through a pretreatment process and dilute acid hydrolysis using microwave irradiation, which is then followed by a fermentation and distillation process. Surface morphology of Ulva reticulata macroalgae samples were analyzed using Scanning Electron Microscopy (SEM). Reducing sugars were analyzed using the Dinitrosalicylate (DNS) method. Ethanol content was analyzed using Gas Chromatography-Flame Ionization Detector (GC-FID). The results showed that the pretreatment and hydrolysis of dilute acid using microwave irradiation reached the optimum hydraulic time and temperature of 50 minutes and 150, with a reducing sugar concentration of 27.97 g/L and a hydrolysis efficiency of 69.93%. The results of the analysis of the ethanol content of Ulva reticulata fermentation using GC was 7.76%. Bioethanol production from the macroalga Ulva reticulata is expected to be a potential new source of renewable energy because it is not used as food. The results of this study serve as a new source of information for the industry to increase the economic value of the macroalga Ulva reticulata. Keywords: bioethanol, fermentation, microwave irradiation, pretreatment, ulva reticulata.